Effect of captivity and cryopreservation on ROS production in Solea senegalensis spermatozoa. Issue 5 (November 2016) - Valcarce, D G; Robles, V
Abstract : Reactive oxygen species have a great impact on spermatozoa function. Gametes from sole males born in captivity (F1) display lower quality than those from wild individuals. In this paper, the percentage of cells positive for dichlorofluorescein (DCF + ) was determined by flow cytometry in wild and F1 animals, the effect of cryopreservation on DCF + cells was evaluated in both groups and the distribution of H2 O2 within the cell was studied by confocal microscopy. Our results indicated that there are no differences in either viability or DCF + cells between wild and F1 animals when fresh samples were evaluated. However, when data were analyzed considering two different sperm populations in terms of motility, a significant decrease in viability and DCF + cells was reported in low-motile F1 spermatozoa. Cryopreservation did not alter the viability or the presence of DCF + cells in sperm samples from wild animals, but significantly decreased the viability in F1 samples. Distribution patterns of H2 O2 have been established by confocal microscopy in Solea senegalensis spermatozoa: co-localization of H2 O2 with active mitochondria (MitoTracker + ) and co-localization with nuclear DNA (DAPI). Compared with H2 O2 distribution in other marine species such as Scophthalmus maximus, Solea senegalensis spermatozoa showed widespread presence of H2 O2 particularly in the nuclei, which could potentially compromise DNA integrity.